The Trinity: an interdisciplinary symposium on the Trinity - Davis, Stephen T.; Kendall, Daniel; O'Collins, Gerald (Oxford University Press, 1999)
Nineteen scholars from different universities, churches, and continents gathered in New York at Easter 1998 for the Trinity Summit. They are experts in a variety of fields: the Bible, ancient Christian writers, ancient Jewish writers, theology, philosophy, art, and preaching. This book is the result of that meeting: a well-researched, skilfully argued, and at times provocative volume on the belief at the very heart of Christianity: the Holy Trinity.